Banking Security System Using Cyber Security - S. Madhumitha,; Ms. N. Vaishnavi, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The goal of the Intelligent Banking Security System project is to create an advanced security system that protects customer data and banking operations by utilizing cutting-edge technologies.  Conventional security systems are insuffici ent since cyber attacks are becoming more complex.  To provide a dynamic and efficient security system, the system integrates end-to-end encryption, biometric identification, machine learning, and artificial intelligence (AI).  The AI-powered fraud detection engine continuously analyzes transaction patterns to identify unusual activity and stop impending fraud in real time.  While MFA offers additional security, biometric authentication using fingerprint scanning and face recognition safely verifies the user.  Blockchain technology provides transparent and unchangeable transaction log security. The technology of blockchain is used to secure transaction logs with transparency and immutability. The system would be capable of real-time monitoring of threats, anomaly detection, and automated responses to incidents so that security violations can be resolved quickly. This project would serve the purpose not only of increasing security but also of building trust among customers, ensuring regulatory compliance, and ensuring a secure and efficient banking experience.